Canva-Based Digital Materials with Differentiation for Grade V Writing Skills: Bahan Digital Berbasis Canva dengan Pendekatan Berbeda untuk Keterampilan Menulis Siswa Kelas V - Erny Junardi; Sulfasyah; Ratnawati (Academia Open, 2025)
General Background: Writing skills are fundamental competencies in elementary education, essential for fostering literacy, critical thinking, and communication abilities. However, many Grade V students in Cluster II, Ujung Pandang, Makassar, exhibit low proficiency in explanatory text writing. Specific Background: Existing instructional materials lack interactivity, visual appeal, and differentiation, leading to limited student engagement and inadequate support for diverse learning needs. Knowledge Gap: Previous studies have explored digital media for education but have not integrated Canva-based digital materials with a differentiated instructional approach specifically to enhance writing skills in elementary schools. Aim: This research aimed to develop and evaluate Canva-based digital teaching materials using the ADDIE model to improve Indonesian language writing skills among fifth-grade students. Results: The developed materials demonstrated high validity (0.77), practicality (teacher responses: 93%, student responses: 94%), and effectiveness (post-test mastery: 92.38% vs. 15.24% pre-test), significantly enhancing students’ ability to write explanatory texts. Novelty: This study introduces an innovative combination of Canva’s visual capabilities and differentiated instruction, providing adaptive, engaging, and accessible learning experiences for diverse learners. Implications: Findings suggest that integrating digital tools with differentiated pedagogy can substantially improve writing competencies and inform future instructional design in elementary education.Highlight : Canva-based materials with differentiation enhance writing skills of Grade V students. Validity and practicality scores indicate high effectiveness. Learning outcomes improved significantly after implementation. Keywords : Digital Teaching Materials, Canva, Differentiation, Indonesian, Learning Outcomes